Higher BMI and extraversion are associated with greater button-press force in a lab setting - Chang, Baotian; Yang, Songbin; Zhang, Nan (Frontiers in Public Health, 2025)
Surface transmission is a major route for gastrointestinal infections, with risk driven by human touch behaviors and microbial transfer rates. Greater touch force generally increases microbial transfer rates—a pattern supported by previous studies, which suggests that increased force may enhance the potential for surface transmission. This study aims to clarify individual differences in touch force and consider how these differences might relate to microbial transfer potential based on existing evidence. We recruited 115 participants and recorded force during two common touches—typing (complex) and elevator-button presses (simple)—using a touch-sensing device. Demographic attributes and personality traits of the participants were assessed through questionnaires. In simple touches, higher BMI (r = 0.35, 95% CI [0.17, 0.51], p < 0.01; Beta = 0.32, 95% CI [0.10, 0.54], p < 0.05) and extraversion (r = 0.21, 95% CI [0.02, 0.38], p < 0.05; Beta = 0.25, 95% CI [0.03, 0.47], p < 0.05) predicted greater force; no demographic attributes or personality variables influenced complex touches, and sex had no effect. In practical terms, individuals with higher BMI or extraversion may disproportionately contaminate—and be exposed to—high-touch surfaces.